…in order to honor Bacchus as he should be… Tragic death of Minsk Governorate Marshall of Nobility Leon Osztorp (1851) in satirical reflection of Ignacy Legatowicz - Snapkouski, Yury (Laughter, humour, satire, 2024)
The article explores history of the perceived image of one of the brightest leaders of gentry of the Belarusian-Lithuanian region of 19th century – a rich landlord Leon Osztorp (1786–1851), who had been unbroken 24 years (1823–1847) Marshall of Nobility for Minsk Governorate. His unexpected accidental death on the eve of Easter shocked the society and was satirized by local famous satirist, master of epigrams Ignacy Legatowicz (1796–1867).Legatowicz wrote several darkly humorous epigrams on Osztorp’s death, which depicted with a certain phycological depth tendences of social changes connected to end of serfdom era. These epigrams became very popular, being spread orally and literally. At the first part of 20th century, they were used by polish historian Janusz Iwaszkiewicz (1879–1944), Professor of Vilnius University. Iwaszkiewicz published Edward Woyniłłowicz’s memoirs, who was an outstanding contemporary (and Leon Osztorp’s godson). These memoirs were contributed by Prof. Iwaszkiewicz placed to anti-imperial (anti-Russian) discourse.In the mid-1930s, Legatowicz’s epigrams supplemented by Prof. Iwaszkiewicz’s negative comments towards Osztorp became a subject of a one-way discussion of an elderly Michalina Horwatt, a younger sister of Edward Woyniłłowicz. She was the second wife of Leon Osztorp’s son-in-law, Otton Horwatt. Being an important source of oral history but hardly grasping the essence of satire, Michalina Horwatt presented her own biased view of Leon Osztorp’s personality.